Polychlorinated Biphenyls Water Pollution along the River Nile, Egypt - Ayman Mohamed Megahed; Hesham Dahshan; Mahdy A. Abd-El-Kader; Amr Mohamed Mohamed Abd-Elall; Mariam Hassan Elbana; Ehab Nabawy; Hend A. Mahmoud (The Scientific World Journal)
Ten polychlorinated biphenyl (PCB) congeners were determined in water samples collected along the River Nile using gas chromatography-electron capture detector (GC-ECD). PCB concentrations ranged from 14 to 20 μg/L, which were higher than those reported in previous studies, indicating serious PCB pollution in the River Nile. PCB congener profiles varied depending on the sampling sties. PCB-138 was the predominant congener accounting for more than 18% of total PCBs. The composition of PCB congeners in the water revealed that highly chlorinated PCB technical mixtures such as Aroclor 1254 was the main PCB production historically used in Egypt. An increasing trend in PCB levels from the upper stream to the Nile estuaries was observed. The calculated flux of PCBs indicated that 6.8 tons of PCBs is dumped into the Mediterranean Sea each year from the River Nile. The hazard quotients and carcinogenic risk caused by PCB pollution in the River Nile were above the acceptable level indicating that PCBs in the River Nile water pose adverse health effects for all age groups. Our findings revealed that PCBs possess a serious risk to the Egyptian population that depends mainly on the River Nile as a source of water. Thus, stricter legislation and regulatory controls should be applied to reduce the risk of PCBs in Egypt.